Property evaluation of spin coated Al doped ZnO thin films and Au/AZO/FTO Schottky diodes - Chaitra, U.; Muhammed Ali, A.V.; Mahesha, M.G.; Kompa, Akshayakumar; Kekuda, Dhananjaya; Mohan Rao, K. (Superlattices and microstructures, 2021)
In the present work, the structural, optical and electrical properties of pristine and aluminium doped zinc oxide (AZO) thin films deposited on fluorine doped tin oxide (FTO) coated glass substrates by sol-gel spin coating technique are explored. Further, the effect of doping on the performance of Au/AZO/FTO Schottky diode were analysed through I–V characterization at room temperature. The c-axis orientation of the deposited films was confirmed by X-Ray diffraction studies. Micrographs from atomic force microscope revealed the wrinkled morphology and columnar structure for undoped and doped zinc oxide thin films respectively. The diode parameters such as Schottky barrier height (ΦB), ideality factor (n) and series resistance (Rs) were determined by using thermionic emission model and Cheung's model. These parameters were found to depend on the doping concentration. Devices with undoped and 6 at% aluminium doped ZnO thin films have shown better rectification. •Al doped ZnO thin films deposited by spin coating technique were used in the fabrication of Au/ZnO/FTO Schottky diodes.•The devices with pristine and 6 at% doped ZnO films showed better rectification in comparison with other samples.•The 6 at% AZO thin films showed better Schottky behavior when compared to the undoped ZnO thin films.